Understanding the residual stress distribution through the thickness of atmosphere plasma sprayed (APS) thermal barrier coatings (TBCs) by high energy synchrotron XRD; digital image correlation (DIC) and image based modelling. (15th June 2017) - Li, Chun; Zhang, Xun; Chen, Ying; Carr, James; Jacques, Simon; Behnsen, Julia; di Michiel, Marco; Xiao, Ping; Cernik, Robert
Abstract: Residual stresses are considered to be the driving forces for the in-service failure of TBCs. The residual stress distribution through an APS TBC has been experimentally measured by high energy synchrotron X-ray diffraction (XRD) showing two distinct features. Firstly a discontinuity or 'jump' in the residual stress trend at a depth of approximately 100 μm from the interface. Secondly we observed a much larger stress gradient than that theoretically predicted. To understand these observations the measured residual stress was compared with analytical and finite element models based on the real 2D and 3D microstructure of the coating visualized by scanning electron microscopy (SEM) and high energy X-ray micro-computed tomography (μ-CT). The effect of the pores in the coating and the rumpled interface between the top coat and the bond coat on the residual stress distribution was studied by image based modelling. It was found that the pores did not have an obvious effect on the overall residual stress distribution. The rumpled interface however was primarily responsible for the jump in the trend. This feature was observed to be located at a depth of approximately 120 μm from the surface with an overall magnitude of approximately 200 MPa. The relaxation of the coating upon in-plane compression was investigated by mechanical testing coupled with DIC. These results are in good agreement with the much larger gradients in the measured residual stress distribution. Graphical abstract: Image